Groundwater recharge mechanism in a semi-arid region from southern Tunisia – a hydrogeochemical and isotopic contribution - Abdelkarim, Bilel (2022)
Groundwater resources management is of strategic importance, particularly in arid and semi-arid regions, mainly associated to climatic environment and human pressures. Southeastern Tunisia, particularly Gabès region, is considered as one of the most promising areas for groundwater resources. Groundwater is the main water source used on agriculture and human consumption associated to the Continental Intercalary (CI) and Complex Terminal aquifers but to the interlayers from Ceno-Turonian and Miocene-Pliocene aquifer systems. The Cretaceous and Quaternary aquifer systems are the most exploited on the region. The present study aims to assess the hydrochemistry of the different aquifer systems as a contribution to the recharge mechanisms. Fifteen six groundwater samples were analyzed for major ions, oxygen-18, and deuterium isotopes to assess the hydrochemistry and isotopic characteristics. Results highlighted that Total Dissolved Solids concentration ranges from 300 to 7200 mg/L. However, the cluster analysis reveals two main groups (A and B) with different chemical and isotopic characteristics. Isotope ratios of oxygen (18O) and hydrogen (2H) were applied to identify the recharge mechanism, which showed a relatively depleted 18O and 2H isotopic ratios and a mixing of groundwater from the Djeffara aquifer with deep thermal groundwater from CI. However, depth to groundwater and local geologic structures also contribute to the mixing pattern. A future detailed structural study to detect the location and properties of fractures will be a relevant contribution. Integration of hydrogeochemical and isotopic data provide a better understanding of the geochemical processes that control the groundwater hydrochemistry and recharging of the different aquifer systems in Gabès region and other areas with similar conditions.